SISTEM INFORMASI NILAI SISWA SEKOLAH DASAR SEBAGAI PENUNJANG DALAM PENGAMBILAN KEPUTUSAN - Alamsyah, Alamsyah (SMARTek, 2011)
The purpose of this research is to design the value of Student Information System to support decision making and daily operational requirements, and to compare the effectiveness and efficiency of data processing and presentation of information between existing systems and information in the proposed system. Research conducted in this case is a qualitative descriptive study surveyed the object of research is on the State Primary School Bambalamotu Mamuju north by using data collecting technique is observation, Interview, and Research Library. System is a system created using the MySQL database and Microsoft Visual FoxPro 9.0 as the programming language. System testing was conducted to examine the effectiveness and efficiency of the system referred to the accuracy of the data, presentation of information and data validation of the proposed Information System. So that the data processing and presentation of the report as expected. The results showed that by using a computerized system in data processing and data collection The students more effectively and efficiently than previously existing systems.